Human, Social, and Digital Capital in Educational Development: Evidence from Pasirmae Village - Muhammad Afrizal; Kiki Syarifudin; Robert Markus Zaka Lawang (Ilomata International Journal of Social Science, 2026)
Persistent disparities in educational quality between rural and urban areas frequently stem from limited infrastructure, financial capacity, and access to educational facilities, yet Pasirmae Village exemplifies how community resources are mobilized to support educational continuity. This study aims to interpret how human capital and social capital operate and interact in shaping community-based educational practices in Pasirmae Village, framing digital capital as a contextual supporting factor that facilitates access rather than as a primary analytical construct equal to the others, rather than constructing generalized theoretical models. Employing a qualitative case study design, data were collected through participant observation, document analysis, and in-depth interviews with teachers, school administrators, community leaders, and parents as key informants, with the data analyzed thematically to identify patterns in the roles and interrelations of these capitals. The findings reveal that human capital, reflected in parental educational awareness and educators’ pedagogical competence, functions as the primary driver of learning quality, while social capital manifested in trust, dense social networks, active participation, and the cultural practice of mutual cooperation operates as a reinforcing mechanism that sustains collective educational initiatives, with their relational interaction allowing social cohesion to amplify the effectiveness of individual capacities in addressing local educational constraints while digital capital provides contextual support; this study contributes by providing a context-bound interpretation of how community-derived resources function as an adaptive mechanism in rural education, offering an empirically grounded insight into the micro-level dynamics of educational development in resource-limited settings.